A 21st century communication sciences and disorders program. - Montgomery JK; Dodd JL; Giess S; Barnes K (Perspectives on School-Based Issues, 2010)
The focus of graduate programs in communication sciences and disorders has changed greatly in the last decade to reflect changes in society in general. Newly formed graduate programs must account for these societal changes as they prepare students for practice in the 21st century. This article will discuss what is expected of new graduates, how teaching philosophies influence course content, and how a new graduate program in communication sciences and disorders came to be.